NATIONAL FAMILY CAREGIVER SUPPORT PROGRAM PROCESS EVALUATION: A REVIEW OF PROGRAM OPERATIONS. (11th November 2018) - Gruman, C; Tomisek, A; Robison, J; Shugrue, N; Kunkel, S; Straker, J; Jenkins, S
Abstract: The NFCSP Process evaluation yielded findings that address program assessment/reassessment, service prioritization and performance/monitoring. Data sources include surveys of State Units on Aging (SUA) (n=54; 100% RR), Area Agencies on Aging (AAA) (n=457; 73% RR), and Local Service Providers (LSP) (n=394; 68% RR). The majority of programs are required to complete a standardized caregiver assessment (SUA=57%; AAA=71%), with annual reassessments being the most typical frequency. It is interesting that many SUAs (63%) and AAAs (79%) use assessment data to complete a care plan as well as to guide service prioritization. Eighty-one percent of LSPs assess caregivers, and most have content dedicated to caregiver health. Two-thirds of SUAs (67%) conduct routine program monitoring at the AAA level and most use the results for compliance and planning purposes. Client satisfaction data is collected by 59% of AAAs. Approaches to enhancing this critically important program will be discussed.